2013
DOI: 10.3126/nepjoph.v5i2.8730
|View full text |Cite
|
Sign up to set email alerts
|

Indications for keratoplasty in Nepal: 2005 - 2010

Abstract: Currently, keratitis, either active or healed, is the major indication for keratoplasty, suggesting that improved primary eye health care is necessary to decrease the prevalence of corneal blindness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 14 publications
2
23
1
4
Order By: Relevance
“…For instance, a study in America found only 897 cases of corneal dystrophy among one million people [8]. Few studies have described the prevalence of corneal dystrophy; available resources indicate that corneal dystrophy is a global cause of corneal transplantation even in children [5,21,22]. In this study, the overall prevalence of corneal vascularization was 3.65%, however, there was wide variation across different age groups, and the overall average rate is not suitable for generalization.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…For instance, a study in America found only 897 cases of corneal dystrophy among one million people [8]. Few studies have described the prevalence of corneal dystrophy; available resources indicate that corneal dystrophy is a global cause of corneal transplantation even in children [5,21,22]. In this study, the overall prevalence of corneal vascularization was 3.65%, however, there was wide variation across different age groups, and the overall average rate is not suitable for generalization.…”
Section: Discussioncontrasting
confidence: 57%
“…While conditions, such as posterior embryotoxon and pigment on endothelium, can be helpful in the diagnosis of glaucoma [1,2], some others, such as corneal opacity, corneal dystrophy, and corneal vascularization can reduce vision and cause blindness when severe [3][4][5][6]. There is limited information about the epidemiology of corneal conditions and their prevalence rates vary in different studies [1,2,7,8].…”
Section: Introductionmentioning
confidence: 95%
“…Regardless of the method and the cause, corneal scars have been reported as a leading indication in up to 66% of cases in the developing world. 3,9,[22][23][24] In our series, corneal scars represent the third most common indication and are responsible for 18.9% of all eyes undergoing corneal transplantation, which is in accordance with reports from some developed countries. 1,5,17,19 Considering the tertiary referral profile of our FIG.…”
Section: Trends In Indications For Corneal Transplantationsupporting
confidence: 92%
“…Compared with 9 studies referring to nearly the same period (Table 2), we found these 3 indications to be the most frequent in Western and Middle Eastern countries [30e35], accounting for at least 50% to 70% or more of all indications. On the contrary, statistics from countries in the Far East showed that w60% to 70% of keratoplasties are performed for corneal scarring and infectious keratitis, the most common indications for surgery in such countries [27,36,37].…”
Section: Discussionmentioning
confidence: 98%